Lepidocybium flavobrunneum as a resource of essential fatty acids - Jamal Basmal (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2010)
Lepidocybium flavobrunneumis a pelagic fish with high economical value. Its high price isdue to its nutritional contents that comprise of high unsaturated and low saturated fatty acids. It isreported that the total contents of Saturated Fatty Acids (SFA) in Lepidocybium flavobrunneumisonly 2.9%, while the amount of Unsaturated Fatty Acids are 97.06% that consist of 8.32% ofpolyunsaturated (PUFA) and 88.74% of Monounsaturated Fatty Acids (MUFA). Approximately,0.05% of linolenic acids -3 (C18:3), 0.51% of eicosatrienoic acids -3 (C20:3) and 1.98% ofdocosahexanoic acids -3 (C22:6) comprise the PUFAs; whereas the MUFAs is composed by84.71% of oleic acids -9 (C18:1) and 0.27% of nervonoic acids -9 (C24:1). -6in Lepidocybiumflavobrunneum contains 0.46% of linoleic acids -6 (C18:2), 0.72% of arachidonic acids -6(C20:4) and 0.01% of lauric acids (C20:0).